2015
DOI: 10.1002/mrc.4362
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring oil displacement processes with k‐t accelerated spin echo SPI

Abstract: Magnetic resonance imaging (MRI) is a robust tool to monitor oil displacement processes in porous media. Conventional MRI measurement times can be lengthy, which hinders monitoring time-dependent displacements. Knowledge of the oil and water microscopic distribution is important because their pore scale behavior reflects the oil trapping mechanisms. The oil and water pore scale distribution is reflected in the magnetic resonance T2 signal lifetime distribution. In this work, a pure phase-encoding MRI technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…At a shear rate of 7 s –1 , the viscosity of the polymer solution was 130 mPas. Alcoflood 935 polymer has been widely employed for enhanced oil recovery in laboratory experiments and in field applications. , Control experiments and previous work showed that the contribution of 1 H in the polymer to the solution MR or MRI signal was negligible. , Brine and polymer solutions were degassed under vacuum to remove air before injection into the core plugs. A light mineral oil (Sigma-Aldrich, United States), largely nonpolar, and a crude oil (Stoney Creek Field, Canada) with polar components were employed.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…At a shear rate of 7 s –1 , the viscosity of the polymer solution was 130 mPas. Alcoflood 935 polymer has been widely employed for enhanced oil recovery in laboratory experiments and in field applications. , Control experiments and previous work showed that the contribution of 1 H in the polymer to the solution MR or MRI signal was negligible. , Brine and polymer solutions were degassed under vacuum to remove air before injection into the core plugs. A light mineral oil (Sigma-Aldrich, United States), largely nonpolar, and a crude oil (Stoney Creek Field, Canada) with polar components were employed.…”
Section: Methodsmentioning
confidence: 99%
“…16,31−33 Control experiments and previous work showed that the contribution of 1 H in the polymer to the solution MR or MRI signal was negligible. 22,24 Brine and polymer solutions were degassed under vacuum to remove air before injection into the core plugs. A light mineral oil (Sigma-Aldrich, United States), largely nonpolar, and a crude oil (Stoney Creek Field, Canada) with polar components 34 were employed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations